Farmers' adoption of newly released climate-resilient rice varieties in the coastal ecosystem of Bangladesh: Effectiveness of a head-to-head adaptive trial - Akter, Tahmina; Afrad, Md. Safiul Islam; Habib, Muhammad Ashraful; Zhang, Yating; Sarkar, Md Abdur Rouf; Nayak, Swati; Qin, Xiaodi; McKenzie, Andrew M.; Kamal, Mohammed Zia Uddin (Wiley, 2025)
The adoption of newly released rice varieties in Bangladesh remains slow, particularly in coastal ecosystems, where multiple stressors reduce productivity. Limited knowledge transfer on climate‐resilient varieties has led farmers to favor traditional cultivars over newer ones. Head‐to‐Head Adaptive Trials (HHATs) were introduced to promote the dissemination of improved varieties, but their effectiveness has not been fully assessed. This study evaluates farmers' trait preferences, varietal selection criteria, adoption patterns, key determinants, and the impact of HHATs on varietal adoption in coastal Bangladesh. HHATs were conducted in 2021–2022 and 2022–2023, with data collected from April to June 2023. Using purposive sampling, 50 participant farmers were selected, while 150 neighboring farmers were systematically sampled based on geographic proximity. Findings indicate that yield, taste, and resilience to salinity and drought were the most important traits influencing varietal selection. While farmers valued the superior grain quality and resilience of newer varieties, concerns over yield consistency and climate adaptability led many to continue adopting older varieties. HHATs created spillover effects, encouraging broader adoption among neighboring farmers. Education, farming as a primary occupation, income, commercial farming, extension services, training, social networks, seed access, grain quality, varietal resilience, and market price significantly influenced adoption, while age, low soil fertility, high input costs, and large landholdings were barriers. Propensity score matching analysis confirmed that HHATs increased adoption rates by 11.25%–17.71%, though limited seed distribution hindered widespread adoption. The study highlights the need for targeted policy measures to enhance seed access, extension services, and farmer support to scale up the adoption of climate‐resilient rice varieties.